Usalpharma: A Cloud-Based Architecture to Support Quality Assurance Training Processes in Health Area Using Virtual Worlds. (20th March 2014) - García-Peñalvo, Francisco J.; Cruz-Benito, Juan; Maderuelo, Cristina; Pérez-Blanco, Jonás Samuel; Martín-Suárez, Ana
Abstract : This paper discusses how cloud-based architectures can extend and enhance the functionality of the training environments based on virtual worlds and how, from this cloud perspective, we can provide support to analysis of training processes in the area of health, specifically in the field of training processes in quality assurance for pharmaceutical laboratories, presenting a tool for data retrieval and analysis that allows facing the knowledge discovery in the happenings inside the virtual worlds.